2014
DOI: 10.4161/trla.29629
|View full text |Cite
|
Sign up to set email alerts
|

Translation initiation of the HIV-1 mRNA

Abstract: Translation initiation of the full-length mRNA of the human immunodeficiency virus can occur via several different mechanisms to maintain production of viral structural proteins throughout the replication cycle. HIV-1 viral protein synthesis can occur by the use of both a capdependant and IRES-driven mechanism depending on the physiological conditions of the cell and the status of the ongoing infection. For both of these mechanisms there is a need for several viral and cellular co-factors for optimal translati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 163 publications
(160 reference statements)
0
2
0
1
Order By: Relevance
“…Due to the apparent relevance in driving HIV-1 Gag protein synthesis when cap-dependent translation initiation is hindered [23][24][25][26][27]30], in this study, we focused on understanding the mechanism of translation driven by the IRES that is located within the 5 0 UTR of the HIV-1 full length mRNA (HIV IRES), [25,26,28]. To date, the molecular basis of HIV-1 IRES-mediated translation initiation remains poorly understood (reviewed in [70,71]). The HIV-1 IRES is active in HeLa and COS-7 cells (Figs 1-4), although, relative to other viral IRESs, its activity is low in HeLa cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the apparent relevance in driving HIV-1 Gag protein synthesis when cap-dependent translation initiation is hindered [23][24][25][26][27]30], in this study, we focused on understanding the mechanism of translation driven by the IRES that is located within the 5 0 UTR of the HIV-1 full length mRNA (HIV IRES), [25,26,28]. To date, the molecular basis of HIV-1 IRES-mediated translation initiation remains poorly understood (reviewed in [70,71]). The HIV-1 IRES is active in HeLa and COS-7 cells (Figs 1-4), although, relative to other viral IRESs, its activity is low in HeLa cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 Posisi IRES HIV-1 diketahui terletak pada 5'UTR. 6 Brasey et al melaporkan bahwa aktivitas IRES minimal terdapat pada basa ke 104-336 dari awal 5'UTR dengan 4 domain penting yaitu primer binding site (PBS), dimerization site (DIS), splice donor site (SD), dan packaging signal (Ψ). 3 Aktivitas IRES 5'UTR HIV-1d dilaporkan tinggi dalam mengekspresikan gen pada sel tropisme dari HIV-1 yaitu sel line THP-1 (monosit) dan sel line HPB-ALL (limfosit).…”
Section: Pendahuluanunclassified
“…Ribosome recruitment onto the HIV-1 unspliced mRNA has been shown to occur through capdependent and cap-independent mechanisms (1)(2)(3). Initial studies showed that the highly structured 5´-untranslated region (5´-UTR) present within the full-length unspliced mRNA was inhibitory for translation in cell-free translation systems suggesting that cap-dependent ribosome scanning was not an efficient mechanism of translation initiation operating in HIV-1 transcripts (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%